A university in a process of national construction - (:unkn) unknown (My University, 2017)
The University of Benin (ex Dahomey), studied between 1950 and 2002, is an attempt to contribute to the history of universities in sub-Saharan Africa. The ambition of this research was to show how a university could be a key place in the process of national construction of Dahomey-Benin, following the independence of Africa in 1960. Established in 1970, with mainly to the support of France, the University of Benin, like all those in French-speaking Africa, is marked by a permanent conflict between continuity and rupture with the educational system inherited from the colonial era. The Benin University, conceived as a public institution for the training of elites, is also a center of youth activism and opposition to power, with repercussions on the entire national life. To study the history of the university means ultimately to study the story of the society, youth, elites, power, administration and international relations. To understand the challenges of the transformations of higher education in Benin today, it appears to us, in the light of our own research, to require international collaborations allowing to cross the scales of analysis and to diversify the points of view.
Keywords: African Research